The role of business school professors in addressing today’s ethical crisis in business - Degen, Ronald Jean (REGEPE Entrepreneurship and Small Business Journal, 2026)
Objective: This discussion paper examines the evolving role of business school professors in addressing the persistent ethical crisis in contemporary business. Building on earlier contributions by Degen (2014, 2018), the study seeks to reassess the responsibility of management education in light of recurring corporate scandals, the rise of ESG practices, digital transformation, and increasing societal distrust in corporate leadership. Methodology: The paper adopts a qualitative and interpretive approach, grounded in an extensive critical review of academic literature, institutional reports, and illustrative case studies from Brazil, the United States, and Europe. Rather than empirical testing, the study advances a reflective and analytical argument typical of discussion papers, integrating multiple ethical frameworks such as stakeholder theory, virtue ethics, justice-based approaches, and digital ethics. Relevance: The topic is highly relevant to entrepreneurship and management studies, as ethical failures undermine trust, legitimacy, and long-term value creation within entrepreneurial ecosystems and established corporations alike. The paper responds to growing concerns that business schools continue to reproduce ideologies centered on shareholder primacy, instrumental rationality, and performative ESG, inadequately preparing future leaders for complex ethical challenges. Contribution: The paper contributes by reframing business school professors as central institutional actors in ethical reform, rather than peripheral instructors of standalone ethics courses. It offers a structured set of pedagogical and institutional recommendations aimed at embedding ethical reasoning, moral imagination, and stakeholder-oriented decision-making across management education, thereby advancing debates on responsible entrepreneurship and sustainable governance.